Understanding alcohol consumption across countries. Issue 40 (26th August 2020) - Clements, Kenneth W.; Lan, Yihui; Liu, Haiyan
ABSTRACT: With unpublished data from the International Comparison Program that cover the consumption of three alcoholic beverages in over 150 countries, we analyse drinking patterns around the world with an index-number approach, by estimating a demand system, and by studying the interaction among beverages in generating utility. We consider a separate demand system for each income quartile and find that tastes are not too different across quartiles. Broadly speaking, the results are robust to rolling sub-samples of countries, an alternative demand model and sample selectivity issues. The differences in the cost of alcohol across countries are also investigated, as is its role in affecting the degree of price-sensitivity of consumption.